Sjögren's syndrome. (January 2022) - Dumusc, Alexandre; Rao, Vijay; Bowman, Simon J.
Abstract: Sjögren's syndrome is a systemic autoimmune disorder characterized by focal inflammation of the exocrine glands, leading to dry eyes and dry mouth. Two forms of the syndrome have been defined: primary (pSS), in which dysfunction of the exocrine glands occurs in the absence of other autoimmune diseases; and secondary, in which patients suffer additional autoimmune processes, especially connective tissue disorders such as rheumatoid arthritis, systemic lupus erythematosus and scleroderma. About 70% of patients with pSS have anti-Ro and/or anti-La autoantibodies. Hypergammaglobulinaemia is also common, and a proportion of patients have systemic involvement. Better use of symptomatic therapies can make a big difference to patients, and there is also current interest in whether biologic therapies could be effective in treating pSS.